Peningkatan Kualitas Kesehatan Pesantren Menuju Santri Sehat Ceria (Satria) di Pondok Pesantren Salafiyah Tarbiyah Islamiyah Batang Kabung Kecamatan Koto Tangah Kota Padang - Sovia Susianty; Fitri Mailani; Bunga Permata Wenny; Tiurmaida Simandalahi; Dewi Murni (Warta Pengabdian Andalas, 2022)
It is still rare to provide counselling to students regarding handling health problems in Islamic boarding schools, so there is still much incorrect knowledge among students about handling health problems that often occur in Islamic boarding schools. This service aims to form a Poskestren (Islamic boarding school health post) at the Salafiyah Tarbiyah Islamiyah Islamic Boarding School in Batang Kabung, accompanied by the formation of a cadre of students. The method for carrying out this activity was the socialization of the formation of the Poskestren, which was carried out for teachers at Islamic boarding schools which was carried out on June 21, 2022, followed by training of Poskestren cadres and providing Poskestren rooms and helping to provide simple tools and medicines on July 19, 2022. Poskestren cadre training activities were carried out for 30 students and female students related to first aid handling, fever management, PHBS, and several infectious diseases that often occur in Islamic boarding schools. This training should be carried out continuously so the Poskestren can perform its functions properly.